The analgesic effect of the intravenous administration of acetaminophen for pediatric laparoscopic appendectomy: A comparison of scheduled and on‐demand procedures. Issue 4 (22nd April 2022) - Yano, Keisuke; Muto, Mitsuru; Nagai, Taichiro; Harumatsu, Toshio; Kedoin, Chihiro; Nagano, Ayaka; Matsui, Mayu; Murakami, Masakazu; Sugita, Koshiro; Onishi, Shun; Yamada, Koji; Yamada, Waka; et al.
Abstract: Purpose: The intravenous administration of acetaminophen (IAA) has become standard postoperative analgesic management for pediatric surgery. However, the most effective methods of IAA for postoperative acute appendicitis are unclear. We evaluated the analgesic efficacy of scheduled IAA vs on‐demand IAA for postoperative acute appendicitis. Methods: Ninety‐four patients who underwent laparoscopic appendectomy in our institution between January 2017 and December 2020 were enrolled. The patients were divided into two groups based on the postoperative pain control protocols. The scheduled IAA group (SA group, n = 42) was managed by scheduled IAA and additional on‐demand use of pentazocine as rescue therapy. The on‐demand IAA group (ODA group, n = 52) was managed by on‐demand IAA as the first choice, with pentazocine as the second choice for pain control. The patients' background characteristics, operative results and postoperative outcomes were reviewed. Results: The number of times pain complaints were made per patient per day (NPPD) on postoperative days (POD) 1 and 2 was significantly lower in the SA group than in the ODA group (POD 1; 1.12 ± 1.21 vs 2.62 ± 1.89, p < 0.01; POD 2; 0.45 ± 0.86 vs. 1.31 ± 1.69, p < 0.01). According to pathological findings, NPPD was lower in the SA group than in the ODA group for both phlegmonous appendicitis (0.71 ± 1.01 vs. 2.10 ± 2.13, P < .05) and gangrenous appendicitis (1.33 ± 1.50 vs 2.94 ± 1.68, P < .01). On POD 2, the incidence of gangrenous appendicitis was significantly lower in the SA group than in the ODA group (0.57 ± 0.93 vs 1.78 ± 1.86, P < .01). Conclusions: Scheduled IAA may have favorable efficacy for postoperative pain control after emergency surgery for acute appendicitis in pediatric patients.